Relations in Creation and Christology: A Response to Porter. (17th August 2018) - Case, Brendan
Abstract: In a recent, provocative essay ("Inheriting Wittgenstein's Augustine, " New Blackfriars (February, 2018)), Philip Porter criticizes Augustine's habit of drawing analogies between the embodiment of concepts in language and the Incarnation of the Word as Jesus of Nazareth, suggesting that his distinctions encourage us to drive a wedge between God the Son and the human being, Jesus, whom he is. Porter worries that Augustine succumbs to the linguistic and then theological fantasy that we might peel away the word's flesh, to attain to the Word beneath. He proposes to dissolve this fantasy by way of a Wittgensteinian revision of Augustine's linguistic Christology, eschewing the distinction between the "verbum mentis" and the "verbum vocis, " the better to safeguard the unity of Christ. In what follows, I suggest that while Augustine is indeed tempted toward Christological error by an inappropriate extension of the linguistic analogy, Porter's proposed corrective both neglects important resources from the developed Chalcedonian tradition, and has as its unhappy outcome that "God is robbed of his transcendence, and creation of its true gratuity."